Sosialisasi Implementasi Undang-Undang No. 33 Dan 34 Tahun 1964 Tentang Pertanggung Jawaban Risiko Kecelakaan Lalu Lintas PT. Jasa Raharja Perwakilan Meulaboh, Cabang Aceh - Safrida Safrida; Nodi Marefanda; Desi Maulida; Rachmatika Lestari; Muzakkir Muzakkir; Nila Trisna; Veni Nella Syahputri; Agussalim Agussalim; Risna Dewi (Universitas Teuku Umar, 2021)
AbstractHuman activities are inseparable from various risks, such as road activities that often cause accidents and deaths. Therefore the government established Law No. 33 and 34 of 1964 concerning liability for accident risk carried out by PT. Jasa Raharja . PT. Jasa Raharja is a state-owned enterprise (BUMN) that guarantees traffic accident insurance through compulsory contributions from passengers and mandatory donations from vehicle owners. But many people do not know yet, when an accident occurs the victims blame each other, burden each other or bear all the risks of the accident. Furthermore, many people do not yet clearly know the procedures, requirements and other provisions for obtaining accident compensation. PT. Jasa Raharja, representative of Meulaboh as the institution responsible for providing accident compensation, has carried out a coding program related to the delivery of information or the socialization of the insurance business. This service program was attended by 40 participants from State Administration Science Teuku Umar University students. This dedication targets all participants to understand the material well delivered and be able to be a liaison to the public related to accident recovery information.